Effluent Quality Test On The Communal WWTP in Banda Aceh City - Ikhwanul Muslimin; Izarul Machdar; Nasrul Arahman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Abstract: One of the domestic wastewater management systems developed in Banda Aceh City is a settlement-scale centralized wastewater treatment plant, also known as the Communal WWTP system, with an anaerobic baffled reactor (ABR) and anaerobic filter (AF) configuration. This study aims to examine the quality of the effluent from the treatment of communal WWTPs in the city of Banda Aceh. Measurements of the contents of pH, BOD, COD, TSS, Ammonia, and Total Coliform were carried out on effluent samples from the communal WWTP and the results of the analysis were compared with the quality standards from the Minister of Environment and Forestry Regulation No. 68 of 2016 concerning Domestic Wastewater Quality Standards. The research showed that the pH, COD, BOD, and Ammonia parameters had met the quality standards, while the TSS and Total Coliform parameters at the five (5) locations of the communal WWTP studied had not shown effective performance and had not met the quality standards. The choice of technology configuration and management of communal WWTP is a factor that influences the processing performance and quality of communal WWTP effluent in Banda Aceh City.Abstrak: Salah satu sistem pengelolaan air limbah domestik yang dikembangkan di Kota Banda Aceh adalah SPALD-Terpusat skala permukiman, atau disebut juga dengan sistem IPAL Komunal, dengan konfigurasi anaerobic baffled reactor (ABR) dan anaerobic filter (AF). Penelitian ini bertujuan untuk menguji kualitas efluen hasil pengolahan IPAL komunal yang ada di kota Banda Aceh. Pengukuran kandungan pH, BOD, COD, TSS, Amonia serta Total Coliform dilakukan pada sampel efluen dari IPAL komunal dan hasil analisisnya dibandingkan dengan baku mutu Peraturan Menteri Lingkungan Hidup dan Kehutanan No. 68 Tahun 2016 tentang Baku Mutu Air Limbah Domestik. Penelitian menunjukkan parameter pH, COD, BOD dan Amonia telah memenuhi baku mutu sedangkan parameter TSS dan Total Coliform pada lima (5) lokasi IPAL komunal yang diteliti belum menunjukkan kinerja yang efektif dan belum memenuhi standar baku mutu. Pemilihan konfigurasi teknologi dan pengelolaan IPAL komunal menjadi faktor yang mempengaruhi kinerja pengolahan dan kualitas efluen IPAL komunal di Kota Banda Aceh.